2012
DOI: 10.1007/s00256-012-1520-4
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography properties of vastus lateralis and vastus medialis obliquus muscles in normal subjects and female patients with patellofemoral pain syndrome

Abstract: We found a significant VMO weakness, and this method may provide quantitative data that might influence the diagnosis of muscle weakness, in female patients with PFPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 26 publications
4
56
5
1
Order By: Relevance
“…While measurements in muscle at rest give an interesting physiological baseline, stiffness of contracted or stretched muscle are more likely to show differences between healthy and pathologic muscles (Botanlioglu et al, 2013); indeed, most clinical qualitative examinations are based on the response of the muscle to an external mechanical solicitation. Voluntary contraction, however, is difficult to reliably reproduce and maintain during the measurement.…”
Section: Introduction and Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…While measurements in muscle at rest give an interesting physiological baseline, stiffness of contracted or stretched muscle are more likely to show differences between healthy and pathologic muscles (Botanlioglu et al, 2013); indeed, most clinical qualitative examinations are based on the response of the muscle to an external mechanical solicitation. Voluntary contraction, however, is difficult to reliably reproduce and maintain during the measurement.…”
Section: Introduction and Literaturementioning
confidence: 99%
“…Clinically, SWE has been used in a recent study to evaluate subject muscles with patellofemoral pain syndrome (Botanlioglu et al, 2013). It has been shown that vastus medialis obliquus of pathologic patients appeared less stiff during contraction than healthy patients but no reliability study was performed.…”
Section: Introduction and Literaturementioning
confidence: 99%
“…22,23 A new technique, shear-wave sonoelastography, has recently been commercialized. 10,[24][25][26][27][28][29][30][31][32][33] Shear-wave sonoelastography provides data on tissue stiffness by measuring the propagation speed of shear wave produced by an acoustic radiation force impulse. This technique is expected to lead to a reduction in operator dependency, high reproducibility and quantitative evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, vastus medialis weakness and atrophy (Botanlioglu et al, 2013; Pattyn et al, 2011) and patellar maltracking (Pal et al, 2013; Pal et al, 2011) have been observed in patients exhibiting patellofemoral pain. Additionally, in vitro studies suggest that VM weakness can laterally shift the patella (Lorenz et al, 2012b; Sakai et al, 2000).…”
Section: Discussionmentioning
confidence: 99%